The Role Of Leadership In The Result Of Integrity Assessment Survey In Ministry Of Finance Of The Republic Of Indonesia - Tomi Murtomo; Setyo Riyanto (Universitas Trunojoyo Madura, 2021)
This article reviews the relationship between leadership in the Ministry of Finance of The Republic of Indonesia and the results of the 2020 Integrity Assessment Survey conducted by the Corruption Eradication Commission of The Republic of Indonesia, where the Ministry of Finance obtained an index of 87.86 on a scale of 100.00. This achievement was classified as good because the average achievement index for the ministries/agencies and local governments was 82.6. With the various definitions of leadership, it is generally agreed that leadership plays an essential role in determining the success of an organization or group within the organization. Leaders have the authority to make decisions and in carrying out what has become a decision. In addition, through the authority possessed, the leader plays a role in determining the work culture and values that are embraced and carried out by everyone in the organization in relation to the implementation of work. This article aims to examine the role of leadership in the achievement of integrity assessment surveys in the Ministry of Finance of The Republic of Indonesia. From a theoretical perspective and studies related to leadership that scholars have previously carried out, there is a common thread between leadership and the results of the integrity assessment survey. It is necessary to conduct a more in-depth empirical study to find out how significant leadership contributes to the achievement of the results of the integrity assessment survey.